Legal Conceptual Comparative Analysis Sharia Economics - Muhamad Maulana Darsono; Sofyan Al-Hakim; Iwan Setiawan (al-Afkar, Journal For Islamic Studies, 2023)
In determining the law, the source of Islamic law is the most basic and significant instrument in the process of determining a particular law. In Islam, there are main sources of law, namely the Al-Quran and sunnah, although scholars from the mu'tazilah group believe that the main source of Islamic law is not the Al-Quran and sunnah but reason is more important. The difference in perspective is very interesting to be discussed in the field of comparative economic fiqh. The method of this paper is a study using normative juridical methods, with secondary data types and sources, collected by documentary methods and analyzed with descriptive qualitative, with the aim of finding differentiation and equality between the two different fiqh paradigms related to the sources of Islamic law used in determining a sharia economic law product.